Trend Analysis of Ergonomics in Improving Supply Chain Management Systematic Literature Review in Last Twenty Years: Knowledge Taxonomy - Louah, Soulaiman; Sarir, Hicham (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
The last ten years have seen a rise in scholarly interest in ergonomics in the supply chain management (SCM) discipline because of technological advancements, as it’s possible effects on productivity, worker satisfaction, and overall business success become more apparent. Nevertheless, there aren't many review studies on the subject at hand. To overcome the restriction, the study thoroughly examined the body of research on ergonomics in SCM that is currently available to enhance comprehension of the state of knowledge. This research article examines peer-reviewed works that have been published between 2000 and 2024 and are accessible through the Scopus database. After thoroughly searching the literature using the Scopus database, 84 papers published in 27 peer-reviewed international journals were found. The current study examines the trend of publications in the area of the analysis of ergonomics in sustaining SCM as well as the most well-known and prolific authors and articles. Then, to find topic clusters, a bibliometric analysis was done with VOSviewer as the primary metric tool in this study for visualizing and analyzing the major hotspots and the evolution of ergonomics in SCM research. The using of co-citation analysis and bibliographic coupling to construct the network map uncovers intriguing themes and patterns in the field of ergonomics in SCM and that points to the need for greater international cooperation in tackling this problem. That’s why our work has improved our understanding of ergonomics in SCM, and the results have led to recommendations for further research.